Callicarpa japonica Japanese Beautyberry: FPS92/FP092, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Japanese beautyberry (Callicarpa japonica), a shrub commonly used in eastern and southern landscapes. It details the plant’s characteristics, including its height, spread, leaf arrangement, and fruiting habits. The Japanese beautyberry is noted for its purple berries that persist into fall and its moderate growth rate. It thrives in USDA hardiness zones 6 through 8 and can be planted year-round in zones 7 and 8. The shrub is suitable for various uses such as foundation planting, borders, mass planting, and containers. It is not known to be invasive and has no serious pest issues. The document also highlights the plant’s soil and light requirements, drought tolerance, and potential for winter interest. Original publication date October 1999.